FORMAÇÃO DE PROFESSORES(AS) E RELAÇÕES INTERPESSOAIS: UM ESTUDO EM SÃO BERNARDO DO CAMPO - Freitas, Silvia Perrone de Lima (2009)
The following work investigates the interpersonal relationships between teachers and formers focusing on the PAP Professor de Apoio Pedagógico (Pedagogical Support Teacher), in Sao Bernardo do Campo s City Hall. It analyses the complexity which involves the formative work and verifies the relationships established between the following: hierarchy, formative interventions, relationships of power, teamwork and knowledge vehiculation. By the end of the year, the PAP is evaluated (previously it was done by the group, whereas now it is done by the director) and voted to assume his function in the year that follows, continuing his previous work or not. If not voted, he shall go back to the classroom. It is observable that some PAP s have been managing to be voted and have maintained themselves for ten years in their function. The point of this research is: what leads the former of teachers to achieve such legitimacy within the group? Interviews were made aiming at a methodological approach on Life Stories analyzing the formative and professional courses of seven PAP s (three of which have been in their function since 1998, when the system was created, and four of which have been in their function since 2007). The theoretical references are anchored in António Nóvoa when the identity and self-knowledge of the professor is discussed; Paulo Freire in the approach on dialogicity as a practice of freedom; Madalena Freire when the group s resistance and constitution are analyzed. The research s conclusion points out that in order to conquer the legitimacy of the group, the former must b aware not to fall in the trap of bureaucracy, which has for many years been part of the scholar institutions, promoting the fitting and control, nor imprison him or herself in the arrogance that the managing position might bring about. Also on the way to conquer the legitimacy of the group is the capacity of facing fears and conflicts through dialog as a practice of freedom. In this sense, there is also the building of a formative identity constituted by the careful hearing and sharp observation of the group s movements in an ethical behavior, where the relationships are built through respect, lovingness, faith in men and criticity.(AU)